2019
DOI: 10.1021/jacs.9b11181
|View full text |Cite
|
Sign up to set email alerts
|

Boron and Phosphorus Containing Heterosiliconoids: Stable p- and n-Doped Unsaturated Silicon Clusters

Abstract: Unsaturated silicon clusters (siliconoids) are short-lived intermediates during the transition from molecules to the elemental bulk; stable representatives reiterate surface features of silicon materials. The incorporation of suitable heteroatoms into the cluster scaffold of stable siliconoids extends this analogy to the technological process of silicon doping. Here, we report boron-and phosphorus-containing heterosiliconoids with BSi 5 and PSi 5 core based on the global minimum Si 6 R 6 platform (dubbed benzp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 69 publications
(154 reference statements)
1
39
0
Order By: Relevance
“… 15 Furthermore, functionalization of the benzpolarene-type cluster D at different positions 6 , 18 and the introduction of boron- and phosphorous-based groups, which corresponds to n- and p-type doping of elemental silicon, was achieved. 19 …”
Section: Introductionmentioning
confidence: 99%
“… 15 Furthermore, functionalization of the benzpolarene-type cluster D at different positions 6 , 18 and the introduction of boron- and phosphorous-based groups, which corresponds to n- and p-type doping of elemental silicon, was achieved. 19 …”
Section: Introductionmentioning
confidence: 99%
“…The resonances at 33.5 ( 2 a ), 26.6 ( 2 b ) and 2.3 ppm ( 2 c ) are assigned to the silicon vertex of the former N‐heterocyclic silylene moiety. While siliconoids Si 7 Tip 5 Cp * and Si 8 Tip 5 Cp* [13d] still exhibit a similarly wide 29 Si NMR shift distribution as the Si 6 benzpolarenes, [13c,e] the chemical shifts of 2 a – c for Si7 may seem quite ordinary at first, but are in fact extraordinarily deshielded considering the pentacoordination of Si7. Pentacoordinate silicon atoms containing the same amidinato ligand typically give rise to signals between −124.9 and −82.9 ppm [26] .…”
Section: Methodsmentioning
confidence: 99%
“…We have shown that ligands with free electron lone pairs such as phosphanyl groups (Scheme 1, A ) allow for the attachment of Lewis acidic organometallic fragments, [5, 10, 20] and now focused on the introduction of electron acceptor functions to the sphere of the [Ge 9 ] cluster (Scheme 1, B ). Scheschkewitz and co ‐workers recently reported on the grafting of silicoinoids of general composition Si 6 R 6 with [BH 3 ] − fragments, [21] as well as p‐doping such clusters by a formal exchange of one Si vertex by a boranyl group [22] . These clusters exhibit unsubstituted vertices and thus are conceptually related to Zintl ions [21b] .…”
Section: Methodsmentioning
confidence: 99%
“…Scheschkewitz and co-workers recently reported on the grafting of silicoinoids of general composition Si 6 R 6 with [BH 3 ] À fragments, [21] as well as p-doping such clusters by a formal exchange of one Si vertex by a boranyl group. [22] These clusters exhibit unsubstituted vertices and thus are conceptually related to Zintl ions. [21b] For several reasons we particularly suspected halo-boranes, 1,3,2-diazaborolidines (DABs), as promising candidates for this venture.…”
mentioning
confidence: 99%